Flexible glass product and preparation method thereof
By chemically strengthening and optimizing the composition, flexible glass products with a thickness of 0.03–0.1 mm were prepared, solving the problem of insufficient mechanical strength of flexible glass and achieving a combination of high mechanical strength and excellent bending performance.
Patent Information
- Application Number
- CN202510272781.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-08-01
AI Technical Summary
The mechanical strength of existing flexible glass is difficult to guarantee effectively, and it is prone to breakage, especially during processing and application.
Flexible glass products with a thickness of 0.03–0.1 mm are prepared by chemical strengthening of flexible glass, with a surface compressive stress of 350–900 MPa and a compressive stress layer depth of 5–25 μm. The components include SiO2, Al2O3, Na2O, K2O, RO and clarifying agent, and ion exchange treatment is carried out using a chemical strengthening salt bath.
It improves the impact resistance and hardness of flexible glass, enhances its mechanical properties, and reduces its elastic modulus, ensuring that it can withstand bending while avoiding breakage.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of materials technology, particularly to the field of glass technology. Specifically, this application discloses a flexible glass product and a preparation method thereof. Background Art
[0002] Flexible glass can achieve bending and folding functions due to its good flexibility and ductility, and these properties make it have wide application value in fields such as folding mobile phones and smart wearable devices. Compared with CPI materials, flexible glass has the characteristics of being not easily scratched and having a smooth touch feel. Also, in terms of light transmittance, since CPI is a resin film, the light transmittance is generally less than 90%, and at the same time, it has the common problem that resin materials are prone to aging and yellowing and a decrease in transmittance under ultraviolet or sunlight; while flexible glass with an average visible light transmittance exceeding 91% can bring a better visual experience to users by virtue of the inherent advantages of the glass material. In addition, the glass transition temperature of flexible glass can reach 600 °C, and it is also more excellent than CPI in terms of temperature performance.
[0003] In related technologies, the currently provided flexible glass is all processed by physical or chemical methods, such as through processes like secondary thinning to reduce the thickness of the glass, thereby achieving the purpose of improving the flexibility of the glass. Since the thickness of flexible glass is extremely low, turnover, transportation, and processing during the processing process will cause a large loss in yield. At the same time, microcracks caused by processing will remain on the surface of the flexible glass during the processing process, reducing the mechanical strength of the flexible glass. Any impurities and microcracks will have a negative impact on the flexible glass and are more likely to break in actual applications. Thus, it can be seen that the mechanical strength of the flexible glass provided by related technologies cannot be effectively guaranteed.
[0004] It should be noted that the technologies described in this part are not necessarily technologies that have been previously envisioned or adopted. Unless otherwise specified, any technology described in this part should not be considered as prior art merely because it is included in this part. Similarly, unless otherwise specified, the problems mentioned in this part should not be considered as having been recognized in any prior art. Summary of the Invention
[0005] This application provides a flexible glass product and a preparation method thereof, aiming to solve at least one of the problems in related technologies to a certain extent.
[0006] In the first aspect of this application, a flexible glass product is provided. The flexible glass product is obtained by chemically strengthening a flexible glass based on a preset composition. The thickness of the flexible glass product is 0.03 - 0.1 mm, the surface compressive stress is 350 - 900 Mpa, and the depth of the compressive stress layer is 5 - 25 μm. The composition of the flexible glass, in terms of mole percentage, includes:
[0007] SiO2 greater than or equal to 35% and less than or equal to 65%;
[0008] Al2O3 greater than or equal to 8% and less than or equal to 22%;
[0009] greater than or equal to 17.8% and less than or equal to 24% Na2O;
[0010] Li2O greater than or equal to 0 and less than or equal to 3%;
[0011] K2O greater than or equal to 0 and less than or equal to 6%;
[0012] RO is greater than 0 and less than or equal to 16%, and RO includes at least one of MgO, CaO, SrO, BaO, and ZnO;
[0013] The amount of a clarifier is greater than 0 and less than or equal to 0.3%, and the clarifier includes at least one of SnO2, CeO2, NaCl, and Na2SO4.
[0014] Optionally, the flexible glass meets at least one of the following performance indicators: water resistance is level 1 to 2, acid resistance is level 1; the flexible glass product meets at least one of the following performance indicators: Vickers hardness is 372 to 596 HV 0.1 , elastic modulus is 55~65GPa, shear modulus is 19~27GPa, and Poisson's ratio is 0.22~0.29.
[0015] Optionally, the surface compressive stress is 500-850 MPa; and / or the depth of the compressive stress layer is 9-23.5 μm.
[0016] Optionally, the flexible glass product satisfies the following performance relationship: E v =E*t,E v Greater than or equal to 2.75 and less than or equal to 3.25, where E v represents the surface strain stiffness, E represents the elastic modulus and its unit is GPa, and t represents the thickness and its unit is mm.
[0017] Optionally, the flexible glass product satisfies the following performance relationship: CS / E v Greater than or equal to 179 and less than or equal to 275, where CS represents surface compressive stress.
[0018] Optionally, the components of the flexible glass, expressed in mole percentage, satisfy the following conditions: the total content of SiO2 and Al2O3 is greater than or equal to 50% and less than or equal to 75%.
[0019] Optionally, the components of the flexible glass, in terms of mole percentage, satisfy that the total content of SiO2 and Al2O3 is greater than or equal to 55% and less than or equal to 70%.
[0020] Optionally, RO includes: ZnO greater than 0 and less than or equal to 5%; MgO greater than or equal to 0 and less than or equal to 5%; CaO greater than or equal to 0 and less than or equal to 5%; SrO greater than or equal to 0 and less than or equal to 6%; BaO greater than or equal to 0 and less than or equal to 8%.
[0021] Optionally, RO includes: ZnO greater than 2% and less than or equal to 4%; MgO greater than or equal to 2% and less than or equal to 3%; CaO greater than or equal to 2% and less than or equal to 3%; SrO greater than or equal to 3% and less than or equal to 5%; BaO greater than or equal to 3% and less than or equal to 6%.
[0022] Optionally, the components of the flexible glass, in terms of mole percentage, further include: P2O5 greater than 0 and less than or equal to 20%.
[0023] Optionally, the components of the flexible glass, in terms of mole percentage, further include: P2O5 greater than or equal to 7% and less than or equal to 16%.
[0024] Optionally, the components of the flexible glass, in terms of mole percentage, include: Al2O3 greater than or equal to 12% and less than or equal to 18%; and / or, Na2O greater than or equal to 17.8% and less than or equal to 20%; and / or, Li2O greater than or equal to 0.5% and less than or equal to 2%; K2O greater than or equal to 2% and less than or equal to 4%; and / or, RO greater than or equal to 4% and less than or equal to 10%; and / or, a fining agent greater than or equal to 0.25% and less than or equal to 0.3%.
[0025] Optionally, the thickness of the flexible glass product is 0.05 - 0.075 mm.
[0026] The second aspect of the present application provides a method for preparing a flexible glass product, including:
[0027] Prepare raw materials in corresponding formula ratios according to the components of the flexible glass;
[0028] Mix the raw materials evenly and then melt them according to a preset melting temperature and melting duration to obtain a glass melt;
[0029] The glass melt is gradually cooled to the target temperature and then formed, followed by machining to obtain flexible glass. Among them, the glass composition in mole percentage includes: SiO2 of not less than 35% and not more than 65%; Al2O3 of not less than 8% and not more than 22%; Na2O of not less than 17.8% and not more than 24%; Li2O of not less than 0 and not more than 3%; K2O of not less than 0 and not more than 6%; RO of more than 0 and not more than 16%, and RO includes at least one of MgO, CaO, SrO, BaO, ZnO; clarifying agent of more than 0 and not more than 0.3%, and the clarifying agent includes at least one of SnO2, CeO2, NaCl, Na2SO4.
[0030] The flexible glass is immersed in a chemical strengthening salt bath for ion exchange treatment to obtain a flexible glass product. Among them, the thickness of the flexible glass product is 0.03 - 0.1 mm, the surface compressive stress is 350 - 900 Mpa, and the depth of the compressive stress layer is 5 - 25 μm.
[0031] Optionally, the melting temperature is 1500 - 1650 °C, the melting duration is not less than 30 min, and the target temperature is 900 - 1650 °C.
[0032] Optionally, the chemical strengthening salt bath by mass percentage includes: KNO3 of not less than 60% and not more than 100%; KOH of not less than 0 and not more than 5%; K2CO3 of not less than 0 and not more than 5%; NaNO3 of not less than 0 and not more than 50%; NaOH of not less than 0 and not more than 2%; Na2CO3 of not less than 0 and not more than 3%; LiNO3 of not less than 0 and not more than 10%; Li2CO3 of not less than 0 and not more than 3%.
[0033] Optionally, the temperature of the chemical strengthening salt bath is 350 - 480 °C, and the duration of the ion exchange treatment is 10 - 60 min.
[0034] As can be seen from the above, according to the flexible glass product and preparation method provided by the solution of the present application, the thickness of the flexible glass product is 0.03 - 0.1 mm, the surface compressive stress is 350 - 900 Mpa, and the depth of the compressive stress layer is 5 - 25 μm. It is obtained by chemically strengthening the flexible glass based on a preset composition. The flexible glass includes SiO2 of greater than or equal to 35 mol% and less than or equal to 65 mol%, and Al2O3 of greater than or equal to 8 mol% and less than or equal to 22 mol%, thereby ensuring that the glass itself has good chemical stability to ensure stress storage capacity. Also, the flexible glass includes Na2O of greater than or equal to 17.8% and less than or equal to 24%, thus ensuring that the glass has a relatively high surface compressive stress after chemical strengthening. In addition, the flexible glass product has a relatively thick thickness and has a natural mechanical strength advantage compared to the conventional flexible glass after secondary thinning. By implementing the solution of the present application, the mechanical properties such as the impact resistance and hardness of the flexible glass are fully enhanced.
[0035] It should be understood that the content described in this part is not intended to identify the key or important features of the present application, nor is it used to limit the scope of the present application. The further effects of the above non-conventional optional methods will be described below in combination with specific embodiments. Detailed Embodiments
[0036] To make the objectives, features, and advantages of the present application more obvious and understandable, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative efforts belong to the scope of protection of the present application.
[0037] In the description of the embodiments of the present application, the term "plurality" means two or more, unless otherwise specifically defined; the term "comprising" indicates the presence of the described features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their combinations; the term "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may include three cases: A exists alone, A and B exist simultaneously, and B exists alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship; the term "about" means that the content, size, parameter, etc. are not and need not be precise, and in necessary cases, they can be approximated or higher or lower. Generally speaking, whether or not specifically stated, the content, size, parameter, etc. should be "about" or "approximate"; the terms "preferred" and "optional" do not limit the scope of the present application, nor do they indicate that certain technical features are crucial and essential for the embodiments of the present application, but should be understood as merely indicating specific aspects of the embodiments of the present application.
[0038] Unless specifically indicated in a particular case, the numerical ranges recited in the embodiments of the present application are intended to include the endpoints of the numerical range and all integers and fractions within the range. When describing a certain quantity, solubility or other parameter in the form of a preferred range or a preferred value, it should be understood that any range obtained by combining any preferred range with a preferred range, a preferred value with a preferred value, or a preferred range with a preferred value is equivalently disclosed, without considering whether such pairwise combinations are specifically explained in the embodiments.
[0039] Unless specifically indicated in a particular case, the component contents recited in the embodiments of the present application are all expressed in mole percentage mol%.
[0040] In order to solve, at least to some extent, the problem that the mechanical strength of the flexible glass provided in the related art cannot be effectively guaranteed, an embodiment of the present application provides a flexible glass. The flexible glass product is obtained by chemically strengthening a flexible glass based on a preset composition. Thus, the flexible glass product includes a compressive stress layer extending from the surface to the depth of the ion exchange layer. The thickness of the flexible glass product is 0.03 - 0.1 mm, the surface compressive stress is 350 - 900 Mpa, and the depth of the compressive stress layer is 5 - 25 μm. For the flexible glass before chemical strengthening, its components are in mole percentages and include: SiO2 of not less than 35% and not more than 65%; Al2O3 of not less than 8% and not more than 22%; Na2O of not less than 17.8% and not more than 24%; Li2O of not less than 0 and not more than 3%; K2O of not less than 0 and not more than 6%; RO of more than 0 and not more than 16%, and RO includes at least one of MgO, CaO, SrO, BaO, and ZnO; fining agent of more than 0 and not more than 0.3%, and the fining agent includes at least one of SnO2, CeO2, NaCl, and Na2SO4.
[0041] SiO2 is an important glass - forming oxide, forming an irregular continuous network with the structural unit of silicon - oxygen tetrahedron to become the framework of the glass. In this embodiment, the lower limit of the SiO2 content is 35% and the upper limit is 65%. In some embodiments, the glass composition may contain SiO2 in the following contents: 35%, 37.5%, 40%, 42.5%, 45%, 47.5%, 50%, 52.5%, 55%, 57.5%, 60%, 62.5%, 65%. In some embodiments, the glass composition may also contain SiO2 in the following contents: not less than 37% and not more than 63%, not less than 39% and not more than 61%, not less than 41% and not more than 59%, not less than 43% and not more than 57%, not less than 45% and not more than 55%, not less than 47% and not more than 53%, not less than 49% and not more than 51%.
[0042] Al2O3 belongs to intermediate oxides, which helps to improve the chemical stability of the glass network structure. However, if the content of Al2O3 is higher than a certain value, it will lead to a relatively high elastic modulus of the glass itself, affecting the bendable mechanical properties of the glass. In this embodiment, the lower limit of the Al2O3 content is 8% and the upper limit is 22%; in some embodiments, the glass composition may contain Al2O3 in the following contents: 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%; in some embodiments, the glass composition may also contain Al2O3 in the following contents: greater than or equal to 9% and less than or equal to 21%, greater than or equal to 10% and less than or equal to 20%, greater than or equal to 11% and less than or equal to 19%, greater than or equal to 12% and less than or equal to 18%, greater than or equal to 13% and less than or equal to 17%, greater than or equal to 14% and less than or equal to 16%. In the preferred embodiment of this embodiment, the content of Al2O3 is greater than or equal to 12% and less than or equal to 18%. Based on the optimized design of the Al2O3 content in this embodiment, it can ensure that the glass itself has good chemical stability to ensure the stress storage capacity without self-explosion.
[0043] Li2O, Na2O, and K2O are alkali metal oxides, which can provide free oxygen, play a role in breaking bonds, reduce the viscosity of the glass, and make the glass easy to melt, and can be used as glass fluxes; moreover, they are outer network oxides of the glass, existing in the holes of the glass structure network in the form of ions, and can undergo ion exchange during the chemical strengthening stage to ensure that the glass has a sufficiently high surface compressive stress. In the optional embodiment of this embodiment, for the above alkali metal oxides in this embodiment, specifically, it includes: Na2O greater than or equal to 17.8% and less than or equal to 24%, for example, it may include 17.8%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or any range formed by taking these values as endpoints of Na2O; Li2O greater than or equal to 0 and less than or equal to 3%, for example, it may include 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any range formed by taking these values as endpoints of Li2O; K2O greater than or equal to 0 and less than or equal to 6%, for example, it may include 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% or any range formed by taking these values as endpoints of K2O. It is worth mentioning that the preferred content of Na2O is greater than or equal to 17.8% and less than or equal to 20%; the preferred content of K2O is greater than or equal to 2% and less than or equal to 4%; the preferred content of Li2O is greater than or equal to 0.5% and less than or equal to 2%.
[0044] It should be noted that the addition of Na2O is to achieve the exchange of sodium ions in the glass with potassium ions in the strengthening salt during the chemical strengthening process, and through the "plugging" effect, compressive stress on the glass surface and inside is achieved. The content of Na2O partly determines the efficiency of the ion exchange process and the maximum surface compressive stress that can be generated. Based on the content of Na2O in the above improved design of this embodiment, it can ensure that the glass has a sufficiently high surface stress after chemical strengthening. In addition, it should also be noted that adding a small amount of K2O and Li2O can improve the chemical stability of the glass through the mixed alkali effect. However, if the addition amount is too high, it will result in a lower glass viscosity, causing crystallization and being unfavorable for the implementation of one-step forming production methods such as the overflow down-draw method. In addition, it should also be noted that when the molar ratio of Na2O to Al2O3 in the glass is greater than 1, alumina tetrahedrons are formed and form a continuous structural network with silica tetrahedrons. When the molar ratio of Na2O to Al2O3 in the glass is less than 1, octahedrons are formed, which are network modifiers and are located in the cavities of the silica structural network.
[0045] RO are divalent oxides such as MgO, BaO, SrO, CaO, ZnO, etc. The flexible glass of this embodiment includes at least one of the above divalent oxides, which can regulate the medium and low temperature viscosity and chemical stability of the glass. In addition, the addition of ZnO can significantly reduce the elastic modulus of the glass itself and improve the bendable mechanical properties of the glass itself. The contents of MgO, BaO, SrO, and CaO should not be too high, otherwise it is easy to increase the elastic modulus of the glass itself and reduce the bendable mechanical properties of the glass itself. In this embodiment, the lower limit of the RO content is greater than 0 and the upper limit is 16%; in some embodiments, the glass composition may contain RO in the following contents: 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%; in some embodiments, the glass composition may also contain RO in the following contents: greater than or equal to 1% and less than or equal to 16%, greater than or equal to 2% and less than or equal to 15%, greater than or equal to 3% and less than or equal to 14%, greater than or equal to 4% and less than or equal to 13%, greater than or equal to 5% and less than or equal to 12%, greater than or equal to 6% and less than or equal to 11%, greater than or equal to 7% and less than or equal to 10%, greater than or equal to 8% and less than or equal to 9%. In the preferred embodiment of this embodiment, the content of RO is greater than or equal to 4% and less than or equal to 10%.
[0046] In an alternative embodiment of the present embodiment, for the above-mentioned various divalent oxides, their contents may be specifically as follows: ZnO greater than 0 and less than or equal to 5%; MgO greater than or equal to 0 and less than or equal to 5%; CaO greater than or equal to 0 and less than or equal to 5%; SrO greater than or equal to 0 and less than or equal to 6%; BaO greater than or equal to 0 and less than or equal to 8%. Preferably, the contents are as follows: ZnO greater than 2% and less than or equal to 4%; MgO greater than or equal to 2% and less than or equal to 3%; CaO greater than or equal to 2% and less than or equal to 3%; SrO greater than or equal to 3% and less than or equal to 5%; BaO greater than or equal to 3% and less than or equal to 6%. It is worth mentioning that on the basis of the above content design of 0 < ZnO ≤ 5% in this embodiment, further combined with the foregoing content design of 0 < P2O5 ≤ 20%, the elastic modulus of the glass itself can be reduced as much as possible, thereby improving the bendable mechanical properties of the glass product.
[0047] The fining agent includes at least one of SnO2, CeO2, NaCl, and Na2SO4, which can reduce the number of internal residual bubbles in the glass during melting, play a role in fining the glass melt, and reduce defects such as bubbles inside the glass. In this embodiment, the lower limit of the fining agent content is greater than 0, and the upper limit is 0.3%; in some embodiments, the glass composition may contain fining agents in the following contents: 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%; in some embodiments, the glass composition may also contain fining agents in the following contents: greater than or equal to 0.05% and less than or equal to 0.25%, greater than or equal to 0.1% and less than or equal to 0.2%. In the preferred embodiment of this embodiment, the content of the fining agent is greater than or equal to 0.25% and less than or equal to 0.3%.
[0048] In an alternative embodiment of the present embodiment, the components of the above flexible glass, in terms of mole percentage, further include: P2O5 greater than 0 and less than or equal to 20%.
[0049] P2O5 is a minor component of the network formers in the glass. P2O5 exists in the form of tetrahedrons in the glass network structure. It forms the structural network of phosphate glass with phosphorus-oxygen tetrahedrons, which can achieve a good fluxing effect and improve the dispersion coefficient and ultraviolet transmittance of the glass. However, when the addition amount is too large, it is likely to cause phase separation of the glass and reduce the chemical stability of the glass. In addition, the addition of P2O5 can significantly reduce the elastic modulus of the glass itself and improve the bendable mechanical properties of the glass itself. In this embodiment, the lower limit of the P2O5 content is greater than 0 and the upper limit is 20%; in some embodiments, the glass composition may contain P2O5 in the following contents: 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%; in some embodiments, the glass composition may also contain P2O5 in the following contents: greater than or equal to 1% and less than or equal to 19%, greater than or equal to 2% and less than or equal to 18%, greater than or equal to 3% and less than or equal to 17%, greater than or equal to 4% and less than or equal to 16%, greater than or equal to 5% and less than or equal to 15%, greater than or equal to 6% and less than or equal to 14%, greater than or equal to 7% and less than or equal to 13%, greater than or equal to 8% and less than or equal to 12%, greater than or equal to 9% and less than or equal to 11%. In the preferred embodiment of this embodiment, the content of P2O5 is greater than or equal to 7% and less than or equal to 16%; further preferably, the content of P2O5 is greater than or equal to 8% and less than or equal to 14%.
[0050] In the alternative embodiment of this embodiment, the total content of SiO2 and Al2O3 is greater than or equal to 50% and less than or equal to 75%. That is, the lower limit of the total content of SiO2 and Al2O3 in this embodiment is 50% and the upper limit is 75%; in some embodiments, the total content of SiO2 and Al2O3 contained in the glass composition is as follows: 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%; in some embodiments, the total content of SiO2 and Al2O3 contained in the glass composition may also be as follows: greater than or equal to 52% and less than or equal to 73%, greater than or equal to 54% and less than or equal to 71%, greater than or equal to 56% and less than or equal to 69%, greater than or equal to 58% and less than or equal to 67%, greater than or equal to 60% and less than or equal to 65%, greater than or equal to 62% and less than or equal to 63%. In the preferred embodiment of this embodiment, the total content of SiO2 and Al2O3 is greater than or equal to 55% and less than or equal to 70%.
[0051] It is worth mentioning that SiO2 and Al2O3 are the main components of the network formers in the glass. Controlling the sum of the contents of SiO2 and Al2O3 within a certain range can not only ensure the integrity of the network structure and the economy of melting the glass, but also provide appropriate network void sizes and chemical stability required for ion exchange during the chemical strengthening process, as well as the ability of the glass body to store the maximum energy generated during the release of the compressive stress. Based on the above total content of SiO2 and Al2O3 improved and designed in this embodiment, it can ensure that the glass itself has good chemical stability while being able to store the stress generated after chemical strengthening without self-explosion.
[0052] Next, this embodiment also explains the introduction sources of the above oxides. Among them, the introduction source of SiO2 is quartz sand; the introduction source of Al2O3 comes from alumina or aluminum hydroxide or aluminum nitrate; the introduction source of P2O5 comes from Al(PO3)3 and (NH4)2HPO4; the introduction source of MgO comes from MgO or Mg(OH)2; the introduction source of ZnO comes from ZnO or zinc nitrate; the introduction source of BaO comes from BaO; the introduction source of CaO comes from CaO or CaCO3; the introduction source of SrO comes from SrO; the introduction source of Na2O comes from Na2CO3 or NaNO3. The introduction source of K2O comes from K2CO3 or KNO3; the introduction source of Li2O comes from Li2CO3 or LiNO3. Of course, in practical applications, specific introduction sources can be selected from the above introduction sources according to specific requirements to meet the raw material needs.
[0053] In an alternative embodiment of this embodiment, the flexible glass product satisfies the following performance relationship: E v = E * t, E v is greater than or equal to 2.75 and less than or equal to 3.25. Among them, E v represents the surface strain stiffness, also known as the surface stiffness, which is used to characterize the ability of the material to resist deformation in the plane direction. E represents the elastic modulus and the unit is GPa, and t represents the thickness and the unit is mm. Based on this performance relationship, it can be known that on the premise of ensuring the constancy of the surface strain stiffness E v , the elastic modulus E is inversely proportional to the thickness t. That is, the elastic modulus can be reduced after the thickness increases. That is, through the optimized design of the flexible glass formula in this embodiment, the elastic modulus of the glass can be effectively reduced and the bending performance of the glass can be improved. It is worth mentioning that in some embodiments, E v can take 2.75, 2.8, 2.85, 2.9, 2.95, 3.0, 3.05, 3.1, 3.15, 3.2, 3.25 or any value range formed by taking these values as endpoints.
[0054] It should be noted that when flexible glass is stressed, the surface stiffness affects its deformation behavior, that is, it affects the ability of flexible glass to maintain flatness after repeated bending. Strength usually refers to the maximum stress that a material can withstand when stressed, and surface stiffness does not directly determine the strength of the material, but can affect its structural bearing capacity. Toughness is the ability of a material to absorb energy and is usually related to fracture toughness or impact toughness. If the surface stiffness increases, it usually means an increase in rigidity, but may reduce the overall toughness of the material, resulting in easier brittle fracture. Based on this, the surface stiffness claimed in this application is within an optimized design range, which is jointly affected by the elastic modulus and thickness, so as to ensure that the flexible glass has both high strength and toughness. Even when the thickness of the flexible glass increases, relatively excellent strength and toughness can still be obtained.
[0055] In an alternative embodiment of this example, the flexible glass product satisfies the following performance relationship: CS / E v is greater than or equal to 179 and less than or equal to 275, where CS represents the surface compressive stress. It is worth mentioning that in some embodiments, CS / E v can take 179, 180, 181, 182,..., 273, 274, 275 or any range formed by using these values as endpoints.
[0056] In an alternative embodiment of this example, the flexible glass satisfies at least one of the following performance indicators: the water resistance is level 1-2, and the acid resistance is level 1; the flexible glass product satisfies at least one of the following performance indicators: the Vickers hardness is 372-596 HV 0.1 、the elastic modulus is 55-65 GPa, the shear modulus is 19-27 GPa, and the Poisson's ratio is 0.22-0.29. It is worth mentioning that HV 0.1 represents the Vickers hardness measured when the indenter load is 0.1 kg.
[0057] It is worth mentioning that the water resistance test method in this example can be the powder method, that is, the glass sample is crushed into a specific specification and pretreated, then loaded into a volumetric flask containing aged pure water, and then placed in a water bath for heating. After meeting the specific heating temperature and duration, the volumetric flask is taken out and cooled. Next, a certain volume of clear liquid is taken out from the volumetric flask and placed in a conical flask, methyl red indicator is added, and it is titrated with 0.01 mol / L hydrochloric acid standard solution until it turns slightly red. Finally, the water resistance of the glass is rated according to the hydrochloric acid consumption and the amount of alkali precipitated. The water resistance level 1 in this example means that the hydrochloric acid solution consumed per gram of glass particles is less than 0.10 mL / g, and the amount of alkali precipitated per gram of glass particles is less than 31 μg / g particles. The water resistance level 2 means that the hydrochloric acid solution consumed per gram of glass particles is 0.10-0.20 mL / g, and the amount of alkali precipitated per gram of glass particles is 31-62 μg / g.
[0058] The acid resistance test method of this embodiment can be the acid immersion method, that is, crushing the glass sample to a specific specification, pre-treating it, and then immersing it in an acidic solution of a specified concentration, controlling the temperature and time for testing. After that, the sample is taken out to observe the corrosion situation and measure the mass loss rate to evaluate the acid resistance. The acid resistance level 1 of this embodiment means that good corrosion resistance can be shown in common acidic solutions such as sulfuric acid and hydrochloric acid.
[0059] In an alternative embodiment of this embodiment, the surface compressive stress of the flexible glass product is 500 - 850 Mpa. For example, the surface compressive stress can be 500, 510, 520, 530,..., 820, 830, 840, 850 Mpa or any value range formed by taking these values as endpoints; the depth of the compressive stress layer of the flexible glass product is 9 - 23.5 μm. For example, the depth of the compressive stress layer can be 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 23.5 μm or any value range formed by taking these values as endpoints. It is worth mentioning that in this embodiment, the FSM-6000X glass surface stress meter manufactured by Orihara Corporation is used to test the surface compressive stress and the depth of the compressive stress layer, and the measurement method adopted can be the optical waveguide method, the scattered light photoelastic method or a simplified measurement method combining the optical waveguide method and the scattered light photoelastic method.
[0060] It is worth mentioning that in the related art, in order to achieve the bendable mechanical properties of glass products, the acid process is usually used to chemically thin the glass substrate, thinning the glass substrate to 30 μm or even thinner to achieve the purpose of making the glass flexible. However, the thinner the glass thickness, the lower the mechanical strength inevitably. In practical applications, the drop resistance and impact resistance of the glass will be relatively poor. Based on the optimized design of the content of the oxide components in the glass composition of this embodiment, starting from the glass formula level, the elastic modulus of the glass product is effectively reduced and the bending performance of the glass product is improved. Therefore, the thickness of the flexible glass is preferably 0.05 - 0.1 mm, such as 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 mm, and more preferably 0.05 - 0.075 mm. Since the thickness of the glass product is thicker than that of conventional flexible glass, the mechanical strength performance of the glass product is guaranteed, and both the bending performance and effective prevention of cracking can be ensured in practical applications.
[0061] Corresponding to the foregoing product embodiment, an embodiment of the present application also provides a preparation method of flexible glass, which specifically includes the following steps:
[0062] Step A: Prepare raw materials in corresponding formula ratios according to the components of the flexible glass;
[0063] Step B: After uniformly mixing the raw materials, melt them according to a preset melting temperature and melting duration to obtain glass liquid;
[0064] Step C: Gradually cool the glass liquid to the target temperature and then perform shaping, followed by machining treatment to obtain flexible glass.
[0065] Among them, the flexible glass, in terms of mole percentage, includes: SiO2 of not less than 35% and not more than 65%; Al2O3 of not less than 8% and not more than 22%; Na2O of not less than 17.8% and not more than 24%; Li2O of not less than 0 and not more than 3%; K2O of not less than 0 and not more than 6%; RO of more than 0 and not more than 16%, and RO includes at least one of MgO, CaO, SrO, BaO, ZnO; clarifying agent of more than 0 and not more than 0.3%, and the clarifying agent includes at least one of SnO2, CeO2, NaCl, Na2SO4.
[0066] Step D: Immerse the flexible glass in a chemical strengthening salt bath for ion exchange treatment to obtain a flexible glass product.
[0067] Among them, the thickness of the flexible glass product is 0.03 - 0.1 mm, the surface compressive stress is 350 - 900 Mpa, and the depth of the compressive stress layer is 5 - 25 μm.
[0068] It is worth mentioning that the ion exchange treatment refers to chemically strengthening the flexible glass by placing it in a chemical strengthening salt bath, so that the flexible glass forms a compressive stress layer and a tensile stress layer. The chemical strengthening salt bath includes one or more of a sodium ion salt bath, a potassium ion salt bath, and a lithium ion salt bath.
[0069] In an alternative embodiment of the present embodiment, the above melting temperature is 1500 - 1650 °C, the melting duration is not less than 30 min, and the target temperature is 900 - 1650 °C. It should be further noted that when the overflow down-draw forming method is adopted in this embodiment, the target temperature is 900 - 1200 °C, and when the casting forming method is adopted, the target temperature is 1500 - 1650 °C.
[0070] It is worth mentioning that since the flexible glass in this embodiment can still ensure the bending performance even when the thickness is higher than that of conventional flexible glass, there is no need for a post-thinning treatment process such as acid process thinning or polishing thinning after forming, which simplifies the processing flow and reduces the production cost. Preferably, the flexible glass with a thickness of 0.05 - 0.075 mm prepared in this embodiment does not need to go through a thinning process.
[0071] In an alternative embodiment of the present embodiment, the step of gradually cooling the glass liquid to the target temperature and then forming it to obtain flexible glass includes: after gradually cooling the glass liquid to the target temperature, using the overflow down-draw method or the slot down-draw method for forming to obtain flexible glass.
[0072] In practical applications, the glass forming methods include but are not limited to production forming methods such as the float method, the overflow down-draw method, the slot down-draw method, the calendering method, and the secondary down-draw method. It is worth mentioning that the viscosity-temperature characteristics of the flexible glass in the forming stage of this embodiment meet the following indicators: the temperature range is 442-1637 °C, and the viscosity range is 10 14.5 ~10 2.3 dPa·s; and the viscosity-temperature characteristics satisfy the following fitting formula:
[0073]
[0074] where Log P represents viscosity, T represents temperature, and a, b, and c all represent fitting constants. The value range of a is -3.80 to -2.39, the value range of b is 5823.56 to 9179.76, and the value range of c is 208.25 to 539.58.
[0075] In addition, the glass property refers to the temperature difference required for a specific viscosity change. The glass property of the flexible glass in the forming process of this embodiment satisfies: the temperature difference corresponding to the viscosity changing from 10 7.65 dPa·s to 10 4.4 dPa·s ranges from 265 °C to 340 °C. In a preferred embodiment, the temperature difference corresponding to the viscosity changing from 10 7.65 dPa·s to 10 4.4 dPa·s ranges from 245 °C to 320 °C. And there is no exothermic peak on the DSC curve of the flexible glass, which can be understood as that in the process of preparing the flexible glass, in the temperature range of 528-1226 °C and the viscosity range of 10 11.5 ~10 4.4 dPa·s, there is no obvious crystallization.
[0076] It is worth mentioning that the temperature-viscosity characteristics of the glass provided in the related technology currently cannot be matched with the forming method. The reason for the mismatch is that in the glass formula design in the related technology, more attention is paid to the mechanical and optical properties of the glass, rather than taking into account the related requirements in engineering forming. Therefore, in the related technology, when preparing flexible glass, it is not possible to produce flexible glass with the required thickness by a one-time drawing forming method. Therefore, an additional thinning process is required to reach the target thickness, and the production complexity is relatively high.
[0077] In this embodiment, the viscosity-temperature characteristics of the glass are fully considered in the glass formula design. On the premise of meeting the above viscosity-temperature characteristics of this embodiment, the production method of the flexible glass of this embodiment can be expanded, that is, low-cost and efficient one-time forming production methods such as the overflow down-draw method and the slot down-draw method can be used.
[0078] It should be noted that the relationship between glass viscosity and temperature plays a decisive role in the glass manufacturing and processing processes. During the glass processing and manufacturing process, specific viscosity-temperature (viscosity-temperature) characteristics need to be followed to achieve the processing goals. The viscosity-temperature characteristic curve of the glass has a series of characteristic temperature points. As an alternative embodiment, the viscosity-temperature characteristics of the flexible glass in this embodiment during the forming stage are as follows: the clarification temperature is 1410-1637 °C, and the corresponding viscosity is 10 2.3 dPa·s; the melting temperature is 1363-1581 °C, and the corresponding viscosity is 10 2.5 dPa·s; the stirring temperature is 1259-1455 °C, and the corresponding viscosity is 10 3 dPa·s; the starting forming temperature is 1036-1226 °C, and the corresponding viscosity is 10 4.4 dPa·s; the terminating forming temperature is 907-1104 °C, and the corresponding viscosity is 10 5.5 dPa·s; the softening point temperature is 727-933 °C, and the corresponding viscosity is 10 7.65 dPa·s; the dilatometric softening point temperature is 528-750 °C, and the corresponding viscosity is 10 11.5 dPa·s; the annealing point temperature is 476-702 °C, and the corresponding viscosity is 10 13 dPa·s; the annealing temperature is 463-691 °C, and the corresponding viscosity is 10 13.4 dPa·s; the strain point temperature is 442-662 °C, and the corresponding viscosity is 10 14.5 dPa·s.
[0079] In an alternative embodiment of the present embodiment, the chemically strengthened salt bath, by mass percentage, includes: KNO3 of not less than 60% and not more than 100%, KOH of not less than 0% and not more than 5%, K2CO3 of not less than 0% and not more than 5%, NaNO3 of not less than 0% and not more than 50%, NaOH of not less than 0% and not more than 2%, Na2CO3 of not less than 0% and not more than 3%, LiNO3 of not less than 0% and not more than 10%, and Li2CO3 of not less than 0% and not more than 3%. Additionally, one or more additives such as metasilicic acid, diatomaceous earth, and alumina may be added to the chemically strengthened salt bath of the present embodiment. Correspondingly, in an alternative embodiment of the present embodiment, the temperature of the chemically strengthened salt bath is 350 - 480 °C, and the duration of the ion exchange treatment is 10 - 60 min.
[0080] In some embodiments, the chemically strengthened salt bath includes: 50 wt% of KNO3, 5 wt% of KOH, 30 wt% of NaNO3, 2 wt% of NaOH, 3 wt% of Na2CO3, 8 wt% of LiNO3, 2 wt% of Li2CO3; in some other embodiments, the chemically strengthened salt bath includes 50 wt% of KNO3, 5 wt% of KOH, 30 wt% of NaNO3, 1 wt% of NaOH, 2 wt% of Na2CO3, 10 wt% of LiNO3, 2 wt% of Li2CO3; in some other embodiments, the chemically strengthened salt bath includes 60 wt% of KNO3, 4 wt% of KOH, 1 wt% of K2CO3, 20 wt% of NaNO3, 1 wt% of NaOH, 3 wt% of Na2CO3, 8 wt% of LiNO3, 3 wt% of Li2CO3; in some other embodiments, the chemically strengthened salt bath includes 70 wt% of KNO3, 3 wt% of KOH, 2 wt% of K2CO3, 20 wt% of NaNO3, 3 wt% of LiNO3, 2 wt% of Li2CO3; in some other embodiments, the chemically strengthened salt bath includes 40 wt% of KNO3, 4 wt% of KOH, 1 wt% of K2CO3, 50 wt% of NaNO3, 1 wt% of Na2CO3, 4 wt% of LiNO3; in some other embodiments, the chemically strengthened salt bath includes 80 wt% of KNO3, 1 wt% of KOH, 4 wt% of K2CO3, 10 wt% of NaNO3, 5 wt% of LiNO3; in some other embodiments, the chemically strengthened salt bath includes 90 wt% of KNO3, 2 wt% of KOH, 3 wt% of K2CO3, 5 wt% of LiNO3; in some other embodiments, the chemically strengthened salt bath includes 100 wt% of KNO3.
[0081] In this embodiment, the formed flexible glass is chemically strengthened, resulting in a compressive stress layer that extends from the surface to the compressive depth of the flexible glass. The peak compressive stress value of this compressive stress layer is 350 - 900 MPa, and the depth of the compressive stress layer is 5 - 25 μm, effectively enhancing the mechanical properties such as the impact resistance and hardness of the glass product.
[0082] Next, in order to illustrate the technical effects of the flexible glass products in this embodiment, the present application conducted tests on chemically flexible glass with a thickness of 0.05 mm obtained by chemically strengthening flexible glass with different components and contents to measure the characteristics of each flexible glass product. Among them, Examples 1 to 13 in Table 1 show the components and corresponding contents of flexible glass with various different compositions in the present application. Table 2 shows the test results of the elastic modulus of the flexible glass products corresponding to Examples 1 to 13 in Table 1. Table 3 shows the test results of the surface compressive stress of the flexible glass products corresponding to Examples 1 to 13 in Table 1. Table 4 shows the test results of the stress layer depth of the flexible glass products corresponding to Examples 1 to 13 in Table 1. Table 5 shows the test results of the surface strain stiffness E v of the flexible glass products corresponding to Examples 1 to 13 in Table 1. Table 6 shows the test results of the ratio of the surface compressive stress CS to the surface strain stiffness E v of the flexible glass products corresponding to Examples 1 to 13 in Table 1.
[0083] Table 1
[0084]
[0085] Table 2
[0086]
[0087]
[0088] Table 3
[0089]
[0090] Table 4
[0091]
[0092] Table 5
[0093]
[0094] Table 6
[0095]
[0096] In addition, the present application also describes the salt bath formulations and temperature conditions used in the tests of Tables 2 to 6. Among them, the salt bath used in Example 1 includes: 50 wt% KNO3, 5 wt% KOH, 30 wt% NaNO3, 2 wt% NaOH, 3 wt% Na2CO3, 8 wt% LiNO3, 2 wt% Li2CO3, and the salt bath temperature is 480 °C; the salt baths used in Example 2, Example 3, and Example 13 include: 50 wt% KNO3, 5 wt% KOH, 30 wt% NaNO3, 1 wt% NaOH, 2 wt% Na2CO3, 10 wt% LiNO3, 2 wt% Li2CO3, and the salt bath temperatures are all 460 °C; the salt baths used in Example 4, Example 5, and Example 12 include: 60 wt% KNO3, 4 wt% KOH, 1 wt% K2CO3, 20 wt% NaNO3, 1 wt% NaOH, 3 wt% Na2CO3, 8 wt% LiNO3, 3 wt% Li2CO3, and the salt bath temperatures are all 430 °C; the salt baths used in Example 6 and Example 8 include: 70 wt% KNO3, 3 wt% KOH, 2 wt% K2CO3, 20 wt% NaNO3, 3 wt% LiNO3, 2 wt% Li2CO3, and the temperature of the salt bath in Example 6 is 430 °C, and the temperature of the salt bath in Example 8 is 390 °C; the salt bath used in Example 7 includes: 40 wt% KNO3, 4 wt% KOH, 1 wt% K2CO3, 50 wt% NaNO3, 1 wt% Na2CO3, 4 wt% LiNO3, and the salt bath temperature is 410 °C; the salt bath used in Example 9 includes: 80 wt% KNO3, 1 wt% KOH, 4 wt% K2CO3, 10 wt% NaNO3, 5 wt% LiNO3, and the salt bath temperature is 350 °C; the salt bath used in Example 10 includes: 90 wt% KNO3, 2 wt% KOH, 3 wt% K2CO3, 5 wt% LiNO3, and the salt bath temperature is 350 °C; the salt bath used in Example 11 includes: 100 wt% KNO3, and the salt bath temperature is 370 °C.
[0097] From the comparison of the test data of Examples 1 to 13 in Table 2 above, it can be seen that for the flexible glass with different formulations of the present application provided in Table 1 above, by optimizing the contents of the two components of P2O5 and ZnO, the elastic moduli of the unstrengthened flexible glass and the strengthened flexible glass are both controlled within a relatively low range. Among them, the elastic modulus of the unstrengthened flexible glass is 56.37 - 64.72 GPa, the elastic modulus of the flexible glass product strengthened for 20 min is 55.40 - 64.35 GPa, the elastic modulus of the flexible glass product strengthened for 40 min is 55.90 - 63.82 GPa, and the elastic modulus of the flexible glass product strengthened for 60 min is 56.16 - 63.27 GPa. In addition, in this example, a 1-million-cycle dynamic bending test with a bending radius of 1.5 mm was also carried out on the flexible glass corresponding to the formulations of Examples 1 to 13 above, and the final test results all passed the test. Thus, it can be seen that the glass formulation optimized in the present application effectively reduces the elastic modulus of the flexible glass, thereby having relatively excellent bendable mechanical properties.
[0098] From the comparison of the test data of Examples 1 to 13 in Tables 3 and 4 above, it can be seen that for the flexible glass with different formulations of the present application provided in Table 1 above, by optimizing the content of Na2O and the total content of SiO2 and Al2O3, the glass has a sufficiently high surface compressive stress and stress layer depth after chemical strengthening. Among them, the surface compressive stress of the flexible glass product strengthened for 20 min is 559.07 - 848.78 MPa, and the stress layer depth is 9.24 - 14.18 μm; the surface compressive stress of the flexible glass product strengthened for 40 min is 516.97 - 845.40 MPa, and the stress layer depth is 12.83 - 18.89 μm; the surface compressive stress of the flexible glass product strengthened for 60 min is 504.76 - 842.12 MPa, and the stress layer depth is 15.53 - 23.52 μm. In addition, in this example, an 80-mm pen-drop test was also carried out using a pen with a weight of 8 g and a bead core of 0.5 mm, and the flexible glass corresponding to the formulations of Examples 1 to 13 above all passed the test. Thus, it can be seen that the glass formulation optimized in the present application ensures that the flexible glass product has excellent mechanical strength performance and is not prone to cracking in actual application scenarios.
[0099] According to the comparison of the test data of Examples 1 to 13 in Table 5 above, for the flexible glass with different formulations of the present application provided in Table 1 above, the surface strain stiffness of the flexible glass without chemical strengthening is 2.8465 - 3.236, the surface strain stiffness of the flexible glass product after 20 minutes of strengthening is 2.77 - 3.2175, the surface strain stiffness of the flexible glass product after 40 minutes of strengthening is 2.795 - 3.193, and the surface strain stiffness of the flexible glass product after 60 minutes of strengthening is 2.808 - 3.1635. By optimizing the contents of the two components of P2O5 and ZnO in the present application, the elastic modulus of the flexible glass can be significantly reduced. Then, based on the values of the surface strain stiffness provided in the examples, it is allowed to increase the glass thickness, that is, while ensuring the bending performance of the glass, the mechanical strength of the glass can be increased to a large extent by thickening the glass.
[0100] According to the comparison of the test data of Examples 1 to 13 in Table 6 above, for the flexible glass with different formulations of the present application provided in Table 1 above, the ratio of the surface compressive stress to the surface strain stiffness of the flexible glass product after 20 minutes of strengthening is 202.74 - 274.73, the ratio of the surface compressive stress to the surface strain stiffness of the flexible glass product after 40 minutes of strengthening is 184.96 - 272.67, and the ratio of the surface compressive stress to the surface strain stiffness of the flexible glass product after 60 minutes of strengthening is 179.66 - 269.10. Thus, through the optimized design of the content of Na2O and the total content of SiO2 and Al2O3 in the present application, the glass has a sufficiently high surface compressive stress after chemical strengthening, effectively ensuring the mechanical strength of the flexible glass product.
[0101] Based on the above solution of the present application, the thickness of the flexible glass product is 0.03 - 0.1 mm, the surface compressive stress is 350 - 900 Mpa, and the depth of the compressive stress layer is 5 - 25 μm. It is obtained by chemically strengthening the flexible glass based on a preset composition. The flexible glass includes SiO2 of not less than 35 mol% and not more than 65 mol% and Al2O3 of not less than 8 mol% and not more than 22 mol%, so as to ensure that the glass itself has good chemical stability to ensure the stress storage capacity; and, the flexible glass also includes Na2O of not less than 17.8% and not more than 24%, so as to ensure that the glass has a relatively high surface compressive stress after chemical strengthening; in addition, the flexible glass product has a relatively thick thickness and has a natural mechanical strength advantage compared with the conventional flexible glass after secondary thinning. Through the implementation of the solution of the present application, the mechanical properties such as the impact resistance and hardness of the flexible glass are fully enhanced.
[0102] It is also worth mentioning that due to the above performance advantages of the flexible glass provided by the embodiments of the present application, it can be widely used in protective covers of foldable screen electronic devices, smart wearable devices, etc.
[0103] Finally, it should be noted that in the above embodiments, the descriptions of each embodiment have their own focuses. For the parts not detailed in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0104] The above is the description of the flexible glass product and its preparation method provided by the present application. For those skilled in the art, any equivalent replacement made according to the idea of the embodiments of the present application in the specific implementation manner and application scope should be covered by the scope of the claims of the present application. In summary, the content of this specification should not be construed as a limitation to the solution of the present application.
Claims
1. A flexible glass product, characterized in that, The flexible glass product is obtained by chemically strengthening a flexible glass based on a preset composition. The thickness of the flexible glass product is 0.03 - 0.1 mm, the surface compressive stress is 350 - 900 Mpa, and the depth of the compressive stress layer is 5 - 25 μm. The composition of the flexible glass, in mole percentages, includes: SiO2 of not less than 35% and not more than 65%; Al2O3 of not less than 8% and not more than 22%; Na2O of not less than 17.8% and not more than 24%; Li2O of not less than 0 and not more than 3%; K2O of not less than 0 and not more than 6%; RO of more than 0 and less than or equal to 16%, and RO includes at least one of MgO, CaO, SrO, BaO, and ZnO; A fining agent of more than 0 and less than or equal to 0.3%, and the fining agent includes at least one of SnO2, CeO2, NaCl, and Na2SO4.
2. The flexible glass article according to claim 1, wherein The flexible glass meets at least one of the following performance indicators: the water resistance is grade 1-2, and the acid resistance is grade 1; the flexible glass product meets at least one of the following performance indicators: the Vickers hardness is 372-596 HV 0.1 , the elastic modulus is 55-65 GPa, the shear modulus is 19-27 GPa, and the Poisson's ratio is 0.22-0.
29.
3. The flexible glass product according to claim 1, wherein, The surface compressive stress is 500 - 850 Mpa; and / or, the depth of the compressive stress layer is 9 - 23.5 μm.
4. The flexible glass product according to claim 1, wherein Satisfy the following performance relationship: E v = E * t, E v is greater than or equal to 2.75 and less than or equal to 3.25, where E v represents the surface strain stiffness, E represents the elastic modulus with the unit of GPa, and t represents the thickness with the unit of mm.
5. The flexible glass article according to claim 4, wherein, Satisfy the following performance relationship: CS / E v Greater than or equal to 179 and less than or equal to 275, where CS represents the surface compressive stress.
6. The flexible glass article according to claim 1, wherein, The composition of the flexible glass, in mole percentages, satisfies that the total content of SiO2 and Al2O3 is not less than 50% and not more than 75%.
7. The flexible glass article according to claim 1, wherein The composition of the flexible glass, in mole percentages, satisfies that the total content of SiO2 and Al2O3 is not less than 55% and not more than 70%.
8. The flexible glass article according to claim 1, wherein RO Including: ZnO of more than 0 and less than or equal to 5%; MgO of more than or equal to 0 and less than or equal to 5%; CaO of more than or equal to 0 and less than or equal to 5%; SrO of more than or equal to 0 and less than or equal to 6%; BaO of more than or equal to 0 and less than or equal to 8%.
9. The flexible glass article according to claim 1, wherein RO Including: ZnO of more than 2% and less than or equal to 4%; MgO of more than or equal to 2% and less than or equal to 3%; CaO of more than or equal to 2% and less than or equal to 3%; SrO of more than or equal to 3% and less than or equal to 5%; BaO of more than or equal to 3% and less than or equal to 6%.
10. The flexible glass article according to claim 8, wherein The composition of the flexible glass, in mole percentages, further includes: P2O5 of more than 0 and less than or equal to 20%.
11. The flexible glass article according to claim 8, wherein, The composition of the flexible glass, in mole percentages, further includes: P2O5 of not less than 7% and not more than 16%.
12. The flexible glass product according to claim 1, characterized in that, The composition of the flexible glass, in mole percentages, includes: Al2O3 of not less than 12% and not more than 18%; and / or, Na2O of not less than 17.8% and not more than 20%; and / or, Li2O of not less than 0.5% and not more than 2%; K2O of not less than 2% and not more than 4%; and / or, RO of not less than 4% and not more than 10%; and / or, a fining agent of not less than 0.25% and not more than 0.3%.
13. The flexible glass article according to claim 1, wherein, The thickness of the flexible glass product is 0.05 - 0.075 mm.
14. A method for preparing a flexible glass product, characterized in that, Including: Prepare raw materials in corresponding formula ratios according to the composition of the flexible glass; Mix the raw materials evenly and melt them according to a preset melting temperature and melting duration to obtain glass liquid; The glass liquid is gradually cooled to the target temperature and then formed, and then processed by machining to obtain flexible glass; wherein, the flexible glass, in terms of mole percentage, includes: SiO2 of not less than 35% and not more than 65%; Al2O3 of not less than 8% and not more than 22%; Na2O of not less than 17.8% and not more than 24%; Li2O of not less than 0 and not more than 3%; K2O of not less than 0 and not more than 6%; RO of more than 0 and not more than 16%, and RO includes at least one of MgO, CaO, SrO, BaO, ZnO; clarifying agent of more than 0 and not more than 0.3%, and the clarifying agent includes at least one of SnO2, CeO2, NaCl, Na2SO4. The flexible glass is immersed in a chemical strengthening salt bath for ion exchange treatment to obtain a flexible glass product; wherein, the thickness of the flexible glass product is 0.03 - 0.1 mm, the surface compressive stress is 350 - 900 Mpa, and the depth of the compressive stress layer is 5 - 25 μm.
15. The method for preparing a flexible glass product according to claim 14, wherein, The melting temperature is 1500 - 1650 °C, the melting duration is not less than 30 min, and the target temperature is 900 - 1650 °C.
16. The method for preparing a flexible glass product according to claim 14, wherein, The chemical strengthening salt bath, in terms of mass percentage, includes: KNO3 of not less than 60% and not more than 100%; KOH of not less than 0 and not more than 5%; KCO3 of not less than 0 and not more than 5%; NaNO3 of not less than 0 and not more than 50%; NaOH of not less than 0 and not more than 2%; NaCO3 of not less than 0 and not more than 3%; LiNO3 of not less than 0 and not more than 10%; LiCO3 of not less than 0 and not more than 3%.
17. The preparation method of the chemically strengthened flexible glass according to claim 14, characterized in that, The temperature of the chemical strengthening salt bath is 350 - 480 °C, and the duration of the ion exchange treatment is 10 - 60 min.